CLINICAL AND LABORATORY FEATURES OF ACUTE VIRAL HEPATITIS IN THE REPUBLIC OF KARAKALPAKSTAN - Sharibaev Islambek Tursinbaevich (TADQIQOTLAR, 2026)
Acute viral hepatitis (AVH) remains a significant public health concern in the Republic of Karakalpakstan, contributing to high morbidity among adults and children. This study aimed to evaluate the clinical presentations and laboratory findings of patients with AVH in the region. A total of 125 patients with confirmed AVH were included. Clinical symptoms, biochemical parameters, and serological markers were analyzed. Fever, jaundice, and hepatomegaly were the most common clinical manifestations. Elevated levels of alanine aminotransferase (ALT) and aspartate aminotransferase (AST) were observed in 88% and 85% of patients, respectively. Serological tests revealed hepatitis A virus (HAV) in 42%, hepatitis B virus (HBV) in 35%, and hepatitis E virus (HEV) in 18% of cases. These findings provide important insights into the epidemiology and laboratory characteristics of AVH in Karakalpakstan, which may guide early diagnosis, management, and prevention strategies.